Selection and results of the aberration computation and peculiarities of polarizing effect compensation in double UV monochromators for satellite-borne UV ozonometers - Vashchenko, V.; Loza, A.; Patlashenko, Zh. (Functional Materials, 2004)
Results of calculations are presented for optical-mechanical peculiarities of the doub le diffraction monochromator arrangement with dispersion subtraction based on spherical diffraction gratings for remote probing of the Earth’s ozonosphere from space platforms within the 255.5-339.8 nm spectrum range with the aim to obtain global mapping for vertical concentration profiles and total ozone content. Special requirements to the equip -ment installed at space platforms were also taken into account. The double diffraction monochromator, as well as a prismatic one, has its own polarizing impact on the measured radiation. Negligence or non-consideration of monochromator polarizing influence on spec-trometric measurements could cause an error up to 70 %. Experimental results show that the spectral sensitivity dependence on the measured radiation polarization is defined b y the system of dispersion elements and the input aperture value. A source of completely depolarized radiation was used for the measurements. To decrease the polarization effect of UV spectrometer, special depolarizers and polarizing effect compensators had been developed. Measurement results obtained with and without such devices have been com -pared to determine their work efficiency. Measurements were performed for all wavelengths of the spectrometer operating spectral range.